The Relationship between Work Motivation and Improved Performance of Ujoh Bilang Community Health Center Employees - Jumran; Hilda; Arsyawina (Formosa Journal of Science and Technology, 2023)
Human resources or employees in an organization are an important concern in order to achieve organizational success. But not all employees have the skills and skills and work spirit in accordance with the expectations of the organization. This type of research is quantitative with 92 population from Ujoh Biku Puskesmas employees. The study used questionnaires. The time of the study was conducted on February 21 - 25, 2023. The results of this research analysis motivated the improvement of high employee work performance by 82.8% and increase in low employee performance by 17.2%. Meanwhile, low work motivation was to increase high employee work performance by 32.1% and increase in low work performance by 67.9%. Based on the results of the study using the chi square test, a p value of 0.03 (p<0.05) with an OR value of 3.951.